Controlling the Constitutionality of Legislative Ordinance Between The Constitutional Council and the Constitutional Court in Algeria - Missaoui, Hanane (Journal of Legal Studies and Researches, 2022)
This study aims to examine to what extent ordinances are subject to constitutional review, this, According to the Algerian constitutional experience, whether before 2020 when they were subject to the control of the Constitutional Council, even that they were not expressly stipulated, This has been proven by reality, which is insufficient, what prompted the legislator in 2020 to fundamentally amended it, he explicitly stated that they were subject to prior compulsory control by the Constitutional Court.